Pengaruh Lamanya Waktu Fermentasi Menggunakan Aktivator Effective Microorganisme (EM4) Terhadap Kadar Nitrogen (N) Dan Phosfor (P) Pada Pupuk Organik Cair Dari Limbah Kulit Kakao - Putri Rizky; Rika Silvany; Resti Ayu Ningrum (Universitas Islam Sumatera Utara, 2023)
Making liquid organic fertilizer, especially from cocoa shells with the addition of bio activator EM4 (Effective Microorganisms) aims to determine the effect of fermentation time on the content of Nitrogen (N) and Phosphorus (P) in liquid organic fertilizer, as well as determining the effect of bio activator EM4 content on N and P The method for making this liquid organic fertilizer is that cocoa shell waste is crushed before fermentation. Then the bio activator EM4 is prepared for addition to cocoa shell waste which has been reduced in size. Cocoa waste is put into a 500 ml beaker, the EM4 bio activator solution is then evenly put into the beaker. Sampling was carried out based on variations in fermentation time (6 days, 12 days, 18 days and 24 days) as well as variations in the addition of 5 ml and 10 ml of EM4 bio activator. The research results showed that the best N and P levels were obtained on the 18th day of fermentation with a volume of 10 ml of EM4 bioactivator, for a nitrogen content of 1.4% and a phosphorus content of 0.35%. The volume of EM4 bio activator greatly influences the N and P content, because the greater the volume of EM4 bio activator, the higher the N and P levels.ABSTRACT Making liquid organic fertilizer, especially from cocoa shells with the addition of bio activator EM4 (Effective Microorganisms) aims to determine the effect of fermentation time on the content of Nitrogen (N) and Phosphorus (P) in liquid organic fertilizer, as well as determining the effect of bio activator EM4 content on N and P The method for making this liquid organic fertilizer is that cocoa shell waste is crushed before fermentation. Then the bio activator EM4 is prepared for addition to cocoa shell waste which has been reduced in size. Cocoa waste is put into a 500 ml beaker, the EM4 bio activator solution is then evenly put into the beaker. Sampling was carried out based on variations in fermentation time (6 days, 12 days, 18 days and 24 days) as well as variations in the addition of 5 ml and 10 ml of EM4 bio activator. The research results showed that the best N and P levels were obtained on the 18th day of fermentation with a volume of 10 ml of EM4 bioactivator, for a nitrogen content of 1.4% and a phosphorus content of 0.35%. The volume of EM4 bio activator greatly influences the N and P content, because the greater the volume of EM4 bio activator, the higher the N and P levels.